Effect of lipopolysaccharide, skin sensitizers and irritants on thioredoxin-1 expression in dendritic cells: relevance of different signalling pathways - Francisco, V (2010)
Thioredoxin-1 is a ubiquitous protein involved in phenotypical and functional changes in dendritic cells (DC). We investigated the effect of lipopolysaccharide (LPS), skin sensitizers, and irritants on thioredoxin-1 by Western blot and immunofluorescence and on mRNA by real-time PCR. As DC models, we used a skin DC line and DC derived from human blood monocytes. We observed that all tested chemicals increased thioredoxin-1 expression, which is only transient for irritants, being the strongest effect observed for LPS (63 +/- 15%). To address the involvement of thioredoxin-1 in DC maturation, we analysed the effect of an activator of thioredoxin-1 expression, hydrogen peroxide, on CD86 expression, a marker of DC maturation. We found that hydrogen peroxide increases thioredoxin-1 and CD86 expression reinforcing thioredoxin-1 involvement in DC maturation. Because mitogen-activated protein kinases and PI3K are activated upon DC maturation, we also analysed their involvement in thioredoxin-1 modulation. We verified that LPS-induced upregulation of thioredoxin-1 expression was dependent on PI3K pathway.